2016
DOI: 10.1175/jcli-d-15-0063.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Climate Forcings and Feedbacks over the Last Millennium in the CMIP5–PMIP3 Models*

Abstract: The role of radiative forcings and climate feedbacks on global cooling over the last millennium is quantified in the CMIP5–PMIP3 transient climate model simulations. Changes in the global energy budget over the last millennium are decomposed into contributions from radiative forcings and climate feedbacks through the use of the approximate partial radiative perturbation method and radiative kernels. Global cooling occurs circa 1200–1850 CE in the multimodel ensemble mean with pronounced minima corresponding wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 73 publications
7
87
1
Order By: Relevance
“…Whereas model simulations generally reproduce the summer cooling, as well as aspects of regional and delayed responses to volcanic eruptions (Zanchettin et al, 2012Atwood et al, 2016), there are discrepancies between model results and the observed climate evolution, in particular regarding the amplitude of the response to volcanic eruptions (e.g. Brohan et al, 2012;Evans et al, 2013;Wilson et al, 2016;Anchukaitis et al, 2010).…”
Section: Drivers Of Climate Variations During the Cementioning
confidence: 97%
“…Whereas model simulations generally reproduce the summer cooling, as well as aspects of regional and delayed responses to volcanic eruptions (Zanchettin et al, 2012Atwood et al, 2016), there are discrepancies between model results and the observed climate evolution, in particular regarding the amplitude of the response to volcanic eruptions (e.g. Brohan et al, 2012;Evans et al, 2013;Wilson et al, 2016;Anchukaitis et al, 2010).…”
Section: Drivers Of Climate Variations During the Cementioning
confidence: 97%
“…Precisely dated records of ice-cap growth from Arctic Canada and Iceland (Miller et al, 2012) showed that LIA summer cooling and ice growth, potentially linked to volcanic forcing, began abruptly between AD 1275 and 1300, followed by a substantial intensification at AD 1430-1455. Moreover, a recent study about the role of radiative forcings and climate feedbacks on global cooling over the last millennium also concluded that the volcanic forcing is the factor that contributed the most (Atwood et al, 2016).…”
Section: Implications For Lia Origin and Norse Coloniesmentioning
confidence: 99%
“…The former, namely stratospheric aerosols from strong volcanic eruptions, is the most important of these two forcings at the global scale during the preindustrial interval of the CE. Although the impacts persist for only a few years, volcanic forcing from multiple events constitutes the most important contributor to the global centennial-scale cooling observed from 850-1800 CE based on comparisons of single-forcing experiments or through the use of all-forcing simulations in which the contributions from individual forcings are isolated offline (Atwood et al, 2016). For this reason, volcanic eruptions are particularly important for gauging the forced hydroclimatic response in lastmillennium simulations.…”
Section: Natural Forcing Of Hydroclimatementioning
confidence: 99%